Implementing Fully Privately Run Public Schools: Top View - Muhamad Hizam Sheikh Khairuddin, Sheikh; Ismail, Kamaruzzaman; Zainudin, Zalina (International Journal of Engineering and Technology, 2018)
The aim of this paper is to identify the perceptions of teachers and regulators in implementing fully privately run public schools (FPRPS) in Malaysia. Under the Malaysian Educational Blueprint (MEB) 2013 - 2025, it is clearly stated that the programs and activities that would encourage and allow parents, the public and private sectors, NGOs, and society to forge a partnership with the school will benefit especially concerning values education. These school community partnerships can be related to the ninth shift in the Blueprint which is â€œpartnering with parents, community and private sector at scale,â€ although, the emphasis of this shift is more on studentsâ€™ academic progress. This study was conducted for three monthsâ€™ periods, involving 87 teachers and principals (in 13 schools) in the districts of Petaling Utama, Wilayah Bangsar-Pudu and Hulu Langat and 23 regulators in 10 Regulatory Bodies. The method used was in the form of focus group discussion (FGD). The data was processed by using Atlas ti. From the interviews conducted on FPRPS, all of the respondents (i.e. teachers, principals and regulators) indicated that they are ready and willing to accept the FPRPS implementation. This is because FPRS offers huge potential benefits to them. These include improvement in studentsâ€™ skill, teacher training, academic performance, employability, financial support, infrastructures, facilities, security, maintenance, workload, and school efficiency. The study contributes to the development of a new type of school in Malaysia.Â